Vita Activa On The Riverbanks Settlements of Aceh Tamiang: Critical Architecture Study - Rizky Kiky; Adi Safyan; Deni; Hendra A (Faculty of Engineering, Malikussaleh University, 2024)
The settlements along the Lintang River in Aceh Tamiang as the target objects of policy products are only oriented towards the physical housing and environment. Improving their quality of life is neglected because policy products do not side with them. The geographical location of their residence which is vulnerable to natural disasters such as flooding which occurs almost every year has made it difficult for them to leave the riverbank settlement environment. As an approach, a study is needed to be oriented towards their quality of life as a reference for policy products that support improving their quality of life. The literature used to reveal the quality of life of riverbank settlers uses the idea of vita activa which consists of labor, work, and action. Meanwhile, the analytical literature uses the idea of dialectics in the realm of critical architecture on the relationship between the form of riverbank settlements and the way the residents live. The study uses qualitative methods to reveal the phenomenon of residents living based on observations and information from residents as critical architectural analysis units. Based on the analysis results, it was found that they are a low-income society with labor on standard mental and intellectual consumption, work that prioritizes energy performance over intellectual performance and expertise, and action characterizes kinship like tribal society groups that view ties based on social status. The products of the settler's environmental policy will not be sustainable due to the limitations of the quality of life that prioritizes survival over maintaining life